On Determining Factors for Good Research in Biomedical and Health Informatics - Haux, R. (Yearbook of Medical Informatics, 2014)
Objective: What are the determining factors for good research in medical informatics or, from a broader perspective, in biomedical and health informatics?Method: From the many lessons learned during my professional career, I tried to identify a fair sampling of such factors. On the occasion of giving the IMIA Award of Excellence lecture during MedInfo 2013, they were presented for discussion.Results: Sixteen determining factors (df) have been identified: early identification and promotion (df1), appropriate education (df2), stimulating persons and environments (df3), sufficient time and backtracking opportunities (df4), breadth of medical informatics competencies (df5), considering the necessary preconditions for good medical informatics research (df6), easy access to high-quality knowledge (df7), sufficient scientific career opportunities (df8), appropriate conditions for sustainable research (df9), ability to communicate and to solve problems (df10), as well as to convey research results (df11) in a highly inter- and multidisciplinary environment, ability to think for all and, when needed, taking the lead (df12), always staying unbiased (df13), always keeping doubt (df14), but also always trying to provide solutions (df15), and, finally, being aware that life is more (df16).Conclusions: Medical Informatics is an inter- and multidisciplinary discipline “avant la lettre”. Compared to monodisciplinary research, inter- and multidisciplinary research does not only provide significant opportunities for solving major problems in science and in society. It also faces considerable additional challenges for medical informatics as a scientific field. The determining factors, presented here, are in my opinion crucial for conducting successful research and for developing a research career. Since medical informatics as a field has today become an important driving force for research progress, especially in biomedicine and health care, but also in fields like computer science, it may be helpful to consider such factors in relation with research and education in our discipline.
Keywords: Medical informatics; biomedical informatics; health informatics; research; interdisciplinary research; multidisciplinary research.